Caracterização da frota e desembarque de atuns no litoral do Espírito Santo, Brasil - Garcia, Roberta Cardozo de Paiva (2023)
This study aimed to characterize the tuna fleet off the coast of Espírito Santo, Brazil. There were 13 fishing communities monitored, belonging to 11 coastal municipalities. The data were obtained from the Fishing Activity Monitoring Program (PMAP) Database from March/2021 to March/2023. The fishing fleet responsible for catching large quantities of tuna is made up of vessels that use surface hand line, rod and bait and horizontal surface longline fishing equipment. There were 20 main species making up the catches of this fleet, with a production of 5,464.83 tons, around 64% of all fish produced in the state. The average monthly CPUE was 551.54 kg/day, with emphasis on rod and bait equipment. The fishing and operating areas of the analyzed devices extend from the south of Bahia to Rio Grande do Sul, with distances that can reach up to 1300 MN from the coast. The information obtained was fundamental for understanding fishing activity and the performance of the Espírito Santo tuna fleet. These analyzes can contribute to future stock assessments and management and ordering in search of sustainable and efficient use of fishing resources.